EVALUATION OF ROAD MEDIAN CONSTRUCTION ON JALAN HAYAM WURUK KM JBR 3+825 - KM JBR 5+930 JEMBER - Ramadhan, Setio; Hayati, Nunung Nuring; Sulistyono, Sonya (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
In 2013, the construction of road median on JalanHayamWuruk Km Jbr 3+825 – Km Jbr 5+930 Jember caused traffic jam. It was shown by the number of degree saturation increased (DS=92) than without a road median (DS=0.66). This research evaluate the comparison between the sections with median and without mediant, parameter, degree of saturation, fuel cost and safety evaluation. The data collection was carried out directly in rapidity survey, and volume vehicles.The analysing of fuel comparison resulted damage 26.12 %, the same as Rp.206.4,00/knd/km, or raised 2.23 Billion per year. It based on the results of evaluation road median SNI 03-2444-2002, the degree of safety in dimension and installation of road median on km Jbr 3+825 – km Jbr 5+930 was not standarized.